EKSISTENSI TRADISI NGELAWANG DI DESA BUDI MUKTI KECAMATAN DAMPELAS KABUPATEN DONGGALA SULAWESI TENGAH - Ni Gusti Ayu Kadek Ari Noviani; I Gede Made Suarnada; Ni Ketut Ratini (Widya Genitri : Jurnal Ilmiah Pendidikan, Agama dan Kebudayaan Hindu, 2026)
The Balinese Hindu community in Budi Mukti Village has a unique tradition is ngelawang. This Village has experienced social changes due to urbanization and modernization, the Hindu generation is more exposed to outside cultures and migration of people to the city. However, the community, local communities, and government have made various efforts to maintain ngelawang tradition. This research aims to determine factors of existence the ngelawang tradition and process of implementing ngelawang tradition in Budi Mukti Village. The research was conducted using a qualitative approach, studied with structural functional theory and religious theory, data collection methods were carried out using observation, interview, documentation and literature search techniques. Determination of informants using purposive sampling techniques. Data analysis was carried out using data collection analysis techniques, data reduction, data presentation and drawing conclusions. Research results: 1) factors that the existence of the ngelawang tradition in Budi Mukti Village is, a) Social Integrity Factor, b) Cultural Identity Factor, c) Social Stability Factor, d) Social Norms and Regulation Factor, e) Change and Adaptation Factor and 2) the process of implementing ngelawang tradition is, a) Initial Procession, b) Procession of the Implementation, and c) Final Procession of the Implementation of the Ngelawang Tradition.